Purpose-driven innovation : lessons from managing change in the United Nations - Flanding, Jens P.; Grabman, Genevieve Marie, 1975- (Emerald Publishing Limited, 2022)
Purpose-Driven Innovation takes readers inside the UN Lab for Organizational Change and Knowledge (UNLOCK) to discover a new theory of change management, developed to help managers navigate accelerating, global, societal challenges such as the Covid-19 pandemic. Using real UN cases, arranged according to the UN change framework, the authors show how this new theory works in the real world, overcoming bureaucratic obstacles and the challenges of the digital era. This is the first book to set out how change management models work in practice in the context of the Sustainable Development Goals (SDGs). It is an essential primer for all organizations, small and large, public or private, within and outside of the United Nations, working to help achieve the SDGs through organizational change in the wake of crisis.